What Does Bamiyan Tell Us about Muslim Attitudes to Buddhism? Unpacking 'Buddhist- Muslim Conflicts' in Contemporary Asia. (11th September 2015) - Obuse, Kieko
Abstract : The article highlights through a case study of the Taliban's destruction of the Buddha statues of Bamiyan in 2001, that there has been considerable diversity in Muslim attitudes towards Buddhism and Buddha statues, reflecting the variety of political and socio-economic contexts in which they were expressed. It argues that the Taliban's destruction of the Buddhas of Bamiyan cannot be attributed exclusively to theological issues but also reflects political agenda regarding economic concerns.